Kronik revolusi Indonesia - Toer, Pramoedya Ananta, 1925-2006; Toer, Koesalah Soebagyo, 1935-; Kamil, Ediati, 1926- (Jakarta : KPG (Kepustakaan Populer Gramedia) bekerjasama dengan Yayasan Adikarya IKAPI dan the Ford Foundation, 1999)
Chronology of importants events in the five years of Indonesian revolution, 1945-1949
vol. 1. 1945 -- vol. 2. 1946 -- voll. 4. 1948
Includes bibliographical references and indexes
Keywords: Indonesia -- History -- Revolution, 1945-1949 -- Chronology